BEST ONLINE INSTRUCTIONAL PRACTICES: REPORT OF PHASE I OF AN ONGOING STUDY - Keeton, Morris T. (Online Learning, 2004)
This study examines how best practices in online instruction are the same as, or different from, best practices in face-to-face (F2F) instruction. The book Effectiveness and Efficiency in Higher Education for Adults summarizes some 20 years of research on best practices in F2F instruction. The bases of comparison are principles from the KS&G material and from Chickering and Gamson’s “seven principles for good practice in undergraduate education”. A reason for making these comparisons is that the rapid growth of online instruction promises that online instruction may become the largest source of ongoing higher education. Not surprisingly, interest in assessing the quality of online offerings has also grown. The question is increasingly raised: Are postsecondary institutions effectively “doing their old job in a new way?”. One way to answer that question is to analyze the online instructional practices of faculty with the aid of research on patterns of instruction, face-to-face and online. This paper is abbreviated from a February 14, 2002 report by Marisa Collett, Morris Keeton and Vivian Shayne of the Institute for Research and Assessment in Higher Education for the Office of Distance Education and Lifelong Learning at the University of Maryland University College.